The Influence of Human Resource Management and Competency Test Budget on Competency Test Implementation at the Southeast Sulawesi Provincial Health Office - Hariawan Hariawan; La Ode Saafi; Sartini Risky (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: The phenomenon in the field shows various problems related to the implementation of competency tests in Southeast Sulawesi Province. Although competency tests are carried out routinely, the results often do not meet expectations with a low pass rate of participants, indicating problems in the quality of implementation. This attracted researchers to conduct an The Influence of Human Resource Management and Competency Test Budget on Competency Test Implementation at the Southeast Sulawesi Provincial Health Office. Method: Quantitative approach, data were collected using questionnaires. The population in this study was 698 people. The sample in this study was 88 respondents. The data analysis technique used was SEM PLS. Result: Human resources management has a negative and significant influence on the implementation of competency tests in the Southeast Sulawesi Provincial Health Office. The competency test budget has a positive and significant influence on the implementation of competency tests. Conclusion: This research can be used as input to maintain and safeguard key factors that influence the implementation of competency tests in the Health Service environment.